Depressive symptoms in individuals with family members requiring ADL assistance - Junhyun Kwon; Eun-Cheol Park; Woorim Kim; Dong-Woo Choi; Sung-In Jang (Komiyama Printing Co. Ltd, 2019)
Abstract Background The number of patients with depressive symptoms worldwide is increasing steadily, and the prevalence of depression among caregivers is high. Therefore, the present study aimed to identify the effects of individuals' caregiving status with respect to their family members requiring activities of daily living (ADLs) assistance on depressive symptoms among those aged 45 or over. Methods Data were collected from the 2006-2016 using the Korean Longitudinal Study of Aging surveys. Participants were categorized into three groups based on their caregiving status with respect to family members requiring ADL assistance: whether they provided the assistance themselves, whether the assistance was provided by other caregivers, or whether no assistance was required. We analyzed the generalized estimating equation model and subgroups. Results A total of 3744 men and 4386 women were included for the analysis. Men who cared for family members requiring ADL assistance had higher depressive symptoms than those with family members who did not require ADL assistance. Among women, participants who had family members requiring ADL assistance that they themselves or others were providing had higher depressive symptoms than those without family members requiring ADL assistance. Subgroup analysis was conducted based on age, job status, regular physical activities, participation status in social activities, and the number of cohabiting generations. Conclusions The study results indicated higher depressive symptoms among those with family members requiring ADL assistance and those who care for such family members themselves. This suggests that an alternative to family caregiving is necessary, especially for the elderly, regardless of caregiver sex.